1989
DOI: 10.1038/bjc.1989.5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 2-[(aminopropyl)amino] ethanethiol on fission-neutron-induced DNA damage and repair

Abstract: Summary The effect(s) of the radioprotector 2-[(aminopropyl)amino] ethanethiol (WR1065) on fissionneutron-induced DNA damage and repair in V79 Chinese hamster cells was determined by using a neutral filter elution procedure (pH7.2). When required, WR1065, at a final working concentration of 4mM, was added to the culture medium, either 30min before and during irradiation with fission spectrum neutrons (beam energy of 0.85MeV) from the JANUS research reactor, or for selected intervals of time following exposure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As previously referred to other normal organic tissues, this protection probably occurs through a mechanism that eases the capture of WR‐1065 in normal tissues, which are better vascularized than tumoral tissues and have better pH conditions for alkaline phosphatase activity that reduces amifostine (WR‐2721) to its active metabolite (WR‐1065). WR1065 acts as a reactive oxygen species scavenger; it also stabilizes intact DNA inside the normal cell nucleus inhibiting DNA intercalation and breakage caused by antineoplastic drugs and improves the DNA ability to self‐repair (Grdina et al,1989). These findings strongly suggest that alkaline phosphatase is present in the testis in enough quantity to enable the conversion of WR2721 to WR1065.…”
Section: Discussionmentioning
confidence: 99%
“…As previously referred to other normal organic tissues, this protection probably occurs through a mechanism that eases the capture of WR‐1065 in normal tissues, which are better vascularized than tumoral tissues and have better pH conditions for alkaline phosphatase activity that reduces amifostine (WR‐2721) to its active metabolite (WR‐1065). WR1065 acts as a reactive oxygen species scavenger; it also stabilizes intact DNA inside the normal cell nucleus inhibiting DNA intercalation and breakage caused by antineoplastic drugs and improves the DNA ability to self‐repair (Grdina et al,1989). These findings strongly suggest that alkaline phosphatase is present in the testis in enough quantity to enable the conversion of WR2721 to WR1065.…”
Section: Discussionmentioning
confidence: 99%
“…30 The symmetrical disulfide intracellular metabolite, WR33278, avidly binds to DNA and nucleoproteins, whereby it alters topoisomerase and thymidine kinase activities, inhibits endonuclease activation, and modulates cell cycle progression. [31][32][33][34][35] The latter events are believed to result from altered regulation and DNA binding of transcription factors, normally induced in response to cellular stress or oxidative injury. 36 This inherent capacity to modify early response genes or their protein products is shared by other organic thiols such as N-acetyl-L-cysteine and the endogenous redox peptide, thioredoxin.…”
Section: Discussionmentioning
confidence: 99%
“…Amifostine currently is FDA approved and marketed as Ethyol ® for use as a cytoprotective agent during the treatment of these and a growing number of cancer types. Grdina et al [1989a,b] and Kataoka et al [1992] showed that amifostine also functions as an antimutagen, an anticancer agent, and an antimetastatic agent. Grdina et al [1992] demonstrated that the aminothiol, WR151327, protected Hep2G cells against the DNA damaging effects of AZT; these findings were significant because they extended the range of the antimutagenic activity of the aminothiols from the DNA damage effects attributed to radiation, and some chemo-therapeutic agents, to the broader range of DNA lesions associated with exposure to AZT as a representative NRTI.…”
Section: Introductionmentioning
confidence: 99%